Optimization of Interpersonal Communication Training for Effective Communication in TBCC Cares in the Banyuwangi District - Wardani, Rifka Pramudia; Dwi Nanda Rachman; Wulan Syarani Asdam; Eka Sari, Jayanti Dian (Universitas Airlangga, 2024)
Background: Tuberculosis (TBC) is the biggest infectious disease killer in the world. Prevention of TB transmission requires cross-sectoral cooperation by involving the community and establishing two-way communication so that comfortable communication and discussion with each other is formed so that the delivery of health messages in TB prevention and treatment is more effective. One of the community-based approaches to prevent TB can be use a communal approach is health cadres. Aims: This study aims to optimize effectiveness communication in TBC Cares with conducting formation Cadres and interpersonal communication training. Methods: The study methods used are qualitative and quantitative (mixed methods). Quantitative method was conducted by questionnaire distributed to measure the knowledge of cadres. Qualitative method was conducted by focus group discussions (FGD) aims to enhance the learning experience of TBC cadres and cadres to optimize the prevention and treatment regarding tuberculosis to patient, families the patient of TB, and the community. The data was analysed using Paired T Test for Cadre's knowledge. Results: Based on the result score Cadre knowledge on pre-test (mean=74,40, SD=16,85) and post-test (mean=86,80, SD=12,81) and (p=0.000). Conclusion: These results show that there is an effect of increasing knowledge on pre and post the intervention. Cadres' Interpersonal communication training can be used alternative way to optimize in prevention and education TBC cadres in Banyuwangi Regency.